2016
DOI: 10.1021/acs.jpcb.6b09535
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Membrane Protein–Ligand Binding Interactions: The Human Purinergic Platelet Receptor

Abstract: Membrane proteins, due to their roles as cell receptors and signaling mediators, make prime candidates for drug targets. The computational analysis of protein-ligand binding affinities has been widely employed as a tool in rational drug design efforts. Although efficient implicit solvent-based methods for modeling globular protein-ligand binding have been around for many years, the extension of such methods to membrane protein-ligand binding is still in its infancy. In this study, we extended the widely used A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 143 publications
2
42
0
Order By: Relevance
“…Our previous studies have shown that a high protein dielectric constant best reproduces experimental results in MMPBSA calculations when charged ligands/active sites present in globular proteins 118, 124 . A similar conclusion can also be drawn in the tested membrane protein: when the “default” protein dielectric value of 4 is used, the correlation is reduced from 0.79 to 0.75 with INP=1.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…Our previous studies have shown that a high protein dielectric constant best reproduces experimental results in MMPBSA calculations when charged ligands/active sites present in globular proteins 118, 124 . A similar conclusion can also be drawn in the tested membrane protein: when the “default” protein dielectric value of 4 is used, the correlation is reduced from 0.79 to 0.75 with INP=1.…”
Section: Resultsmentioning
confidence: 78%
“…The water relative dielectric constant was set at 80.0. The membrane dielectric constant was set to be 7.0 124 . And the protein dielectric constant was set to be 20.0 due to the presence of charged ligand molecules 118, 124 .…”
Section: Methodsmentioning
confidence: 99%
“…To improve the convergence rate for use in biomolecular applications, the Incomplete Cholesky preconditioning method and the geometric multigrid method were both extended to incorporate periodicity (Botello-Smith and Luo, 2015 ). Applications to protein-ligand binding utilizing the newly developed membrane MMPBSA method were also reported (Greene et al, 2016 ; Xiao et al, 2017 ).…”
Section: Improvements Of Mmpbsamentioning
confidence: 99%
“…All CUDA PBE solvers were implemented in both single and double precisions in the PBSA program 45,46,78,79,[149][150][151][152][153][154][155][156][157][158][159][160][161] of the Amber/AmberTools 18 packages. 162,163 The double precision was implemented for the robustness analysis only, and the single precision was used throughout the study unless otherwise specified.…”
Section: Computational Detailsmentioning
confidence: 99%